1978
DOI: 10.1113/jphysiol.1978.sp012541
|View full text |Cite
|
Sign up to set email alerts
|

Nervous release of vasoactive intestinal polypeptide in the gastrointestinal tract of cats: possible physiological implications.

Abstract: SUMMARY1. The release of vasoactive intestinal polypeptide (VIP) into blood from the gastrointestinal tract was studied when eliciting autonomic nervous effects known to be mediated via non-adrenergic, non-cholinergic nerve fibres. All studies were performed on animals given atropine.2. Electrical stimulation of the low threshold vagal fibres to the stomach did not significantly change gastric volume or VIP concentration in the venous effluent from the stomach. Stimulating the high threshold fibres, on the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(100 citation statements)
references
References 29 publications
(18 reference statements)
7
92
0
1
Order By: Relevance
“…In a recent study it was shown that stimulation of the pelvic nerves to the colon produced a significant increase of vasoactive intestinal polypeptide (VIP) in the venous effluent from the large bowel (Fahrenkrug, Haglund, Jodal, Lundgren, Gibe & Schaffalitzky de Muckadell, 1978) supporting the idea that VIP is a neurotransmitter in the vasodilatation elicited by pelvic nerve stimulation. It has been demonstrated that subthreshold pelvic nerve stimulation as regards blood flow effect increases the capillary filtration coefficient indicating release of a substance which increases capillary permeability (Fasth & Hulten, 1973c).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a recent study it was shown that stimulation of the pelvic nerves to the colon produced a significant increase of vasoactive intestinal polypeptide (VIP) in the venous effluent from the large bowel (Fahrenkrug, Haglund, Jodal, Lundgren, Gibe & Schaffalitzky de Muckadell, 1978) supporting the idea that VIP is a neurotransmitter in the vasodilatation elicited by pelvic nerve stimulation. It has been demonstrated that subthreshold pelvic nerve stimulation as regards blood flow effect increases the capillary filtration coefficient indicating release of a substance which increases capillary permeability (Fasth & Hulten, 1973c).…”
Section: Discussionmentioning
confidence: 91%
“…Inhibitory neurones are present throughout the gut but seems to be KININ SYSTEM AND PELVIC NERVES centrally controlled only in the stomach (Martinsson, 1965) and in the rectum (Fasth et al 1980). In a recent report by Fahrenkrug et al (1978) it was suggested that direct vagal release of VIP is responsible for the gastric receptive relaxation. Whether this hormone might also be involved in the pelvically controlled non-adrenergic relaxation of the large intestine remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Several neurotransmitters have been proposed to mediate these mechanisms including adenosine triphosphate (ATP; Burnstock, 1972), vasoactive intestinal polypeptide (VIP; Fahrenkrug, Haglund, Jodal, Lundgren, Olbe & Schaffalitzky de Muckadell, 1978) and kinins (Fasth, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to assess the VIP concentration in nerve endings, but 10-~ M VIP may be compatible concentration as a neurotransmitter, when we compared with that of venous concentration after nerve stimulation (Fahrenkrug et al 1978). The CCK secretion by VIP was atropine-resistant and similar results were observed with gastrinreleasing peptide (GRP) stimulation (Nakano et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…VIP is mainly located in nerve cells and considered to be one of the neurotransmitters of peptidergic nerves (Said and Rosenberg 1976;Fahrenkrug et al 1978). In an attempt to further elucidate the mechanisms of neural regulation of CCK release, we examined CCK secretion by VIP in an isolated perfused rat duodenum system.…”
mentioning
confidence: 99%